Break-ups and the limits of encoding love - Hogan, B (Routledge, 2018)
This essay explores how social network sites encoded relationships in ways that do not always fit the relationship as lived experience by individuals. This act of encoding is especially salient in acts of the relationship where there is a discrepancy between what is performed (love within the relationship) and what is exhibited (static states that signify the relationship). One critical case of this discrepancy is the break-up, as this process leaves static traces to persist online while individuals live separately. The essay uses examples from television media and psychology, particularly the concept of verbal overshadowing to emphasize the challenge in reconciling performed and exhibited relations. In doing so, this essay highlights that it is not only individual profiles and contributions that are curated on social media systems, but relationships as well. As a consequence, networked societies cannot contain aspects of human experience such as love which are relational and processoriented, but only signify these aspects and seek to steer them. The way they are steered is not necessarily in the interests of the individuals but the platforms. Designing for a break-up further implies considering how to undermine the pervasive logic of connectivity within the ideology of a network society.